Agrobiodiversity of Talas Beneng (Xanthosoma undipes K.Koch) Based-Community Forest and Its Role in The Productivity Enhancement - Suhartono, Suhartono; Yusnikusumah, Tri Rizkiana (Media Konservasi, 2025)
The increasing intensification of agriculture, which tends to be monocultural and lacks attention to diversity, has led to global challenges related to climate change and sustainability by affecting carbon sequestration, land productivity, and farmers' incomes. This study aimed to determine the role of agrobiodiversity in the talas beneng community forest in supporting sustainable agriculture that provides long-term benefits for the environment, economy, and community welfare. We conducted a case study on an agroforestry system based on taro cultivation in community forest land using a vegetation survey, observations, and interviews with three key respondents. The results showed that agroforestry-based taro cultivation has the potential to extend the timber harvesting cycle and maintain the ecosystem functions of community forests. Agrobiodiversity in community forest land based on taro cultivation is relatively low (H' <3), but it can have a positive impact on agricultural land sustainability and potentially increase the local economy and farmers' income.